Dilemmas and Opportunities for Chinese Broadcasters and Presenters in the Era of Media Convergence - Zhang, Yuchan; Tan, Kim Hua; Ponnudurai, Prema; Yunos, Nasruddin; Saad, Suziana Mat; Mohamad, Zulkifli (Journal of Posthumanism, 2025)
In this era of media convergence with rapid technological development, broadcasting practitioners are faced with the problem of how to use new technologies to enhance news dissemination and turn dilemmas into opportunities. This study uses media convergence theory and Chinese broadcasting theory to conduct a collective case study of positive examples of barrier-breaking, analyzing different presenters and their programs. It analyses the impact of changes in how audiences receive information, the relative lag in the speed of communication, the limitations of the form of communication, and the decline in the influence of communication on the communication of broadcasters and presenters. It puts forward positive suggestions in terms of guiding public opinion, strengthening one's influence, adapting to the form of communication, and transforming the language style. This will inform the career development of radio and television industry practitioners in the era of media convergence.